Validated TLC-Contact Bioautography Method for Identification of Kanamycin Sulfate in Injection Preparation - Susanti Susanti; Aprelita Nurelli Dwiana; Febri Annuryanti; Asri Darmawati; Isnaeni Isnaeni (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2020)
Background: TLC-contact bioautography is one of an effective method for identification antibiotics, by which many antibiotics could be identification and determination simultaneously. Objective: To evaluate kanamycin sulfate in injection preparations based on its inhibitory activity against Escherichia coli ATCC 8739 as test organism. Methods: Sample and standard solutions were spotted onto TLC silica gel 60 F254 plate and developed in 10% potassium dihydrogen phosphate solutionas as mobile phase. The TLC-contact bioautography method was  validated according to USP guidelines by considering specificity, LOD, LOQ, linearity, accuracy and precision parameters. Results: The TLC-contact bioautography method was found to be high sensitivity with LOD of 0.75 µg and LOQ 2.31 µg. Linearity range of 100-350 µg/mL with r = 0.9993 and linear regression equation was y = 0.0019x + 0.0338. The recovery obtained from addition of blank samples by three different concentrations of kanamycin sulfate standard was 101.40% ¬+ 2.02%. The precision of the method was good with coefficient of variation 0.080%. The TLC-contact bioautography method was supported by determination of kanamycin sulfate potency ratio in the injection preparation and kanamycin sulfate standard using 3-3 design. Random block design obtained the potential for kanamycin sulfate in injection preparations compared to kanamycin sulfate standard was 100.6%.  Conclusion: The TLC-contact bioautography for kanamycin sulfate in injection preparations could be applied to the quality control analysis of the investigated drugs.